2007
DOI: 10.1177/1087057106296496
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free High-Throughput Functional Lytic Assays

Abstract: Refractive index-sensitive resonant waveguide grating biosensors are used to assay the label-free enzymatic degradation of biomolecules. These assays provide a robust means of screening for functional lytic modulators. The biomolecular substrates in this study were covalently immobilized through amine groups. Using the Corning ® Epic™ System, the digestion signatures for multiple protein substrates on the biosensors are measured. Label-free digestion profiles for these proteins were substrate specific. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The binding of the presented thiazolidinediones to recombinant Bid was measured using the EnSpire label-free platform (Fig. 6, C-E) (O'Malley et al, 2007). Using this biochemical assay, the target Bid was initially immobilized at a concentration of 200 mg/ml onto the aminocoupling surface of the EnSpire label-free biochemical microplate biosensor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of the presented thiazolidinediones to recombinant Bid was measured using the EnSpire label-free platform (Fig. 6, C-E) (O'Malley et al, 2007). Using this biochemical assay, the target Bid was initially immobilized at a concentration of 200 mg/ml onto the aminocoupling surface of the EnSpire label-free biochemical microplate biosensor.…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical assays were performed using the Corning Epic label-free technology on the EnSpire Multimode Plate Reader (PerkinElmer, Rodgau, Germany) (O'Malley et al, 2007). Bid immobilization on the optical biosensors was accomplished by adding 200 mg/ml protein in 20 mM sodium acetate, pH 4.0, using a 12-channel Thermo Scientific matrix multichannel equalizer pipette followed by overnight incubation at 4°C.…”
Section: Label-free Biochemical Assaymentioning
confidence: 99%
“…Particularly, immobilized enzymes can be implemented as an alternative high-throughput screening (HTS) method aimed at identifying novel drug candidates for the treatment of several life-threatening diseases. [6][7][8] Neglected tropical diseases are widely distributed throughout the tropical and subtropical regions of the world, with significant social and economic impact. 9,10 Chagas' disease, caused by the parasite Trypanosoma cruzi, is a parasitic infection widespread in the Americas, from the great lakes of North America to Southern Patagonia, with devastating consequences in terms of human morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Based upon data obtained by SPR, kinetic parameters and equilibrium constants of binding (i.e., on-rate, off-rate, and apparent dissociation constants) can be determined. 7,10,11 A recent study of carbonic anhydrase II that compared SPR with the traditional measurement of stopped-flow fluorescence showed that the kinetic parameters determined by SPR are in agreement with those determined by stopped-flow fluorescence.…”
Section: Optical Sensingmentioning
confidence: 99%
“…8,9 Target protein is immobilized onto a solid surface via covalent or noncovalent interaction. Binding of small-molecule compounds changes the refractive index of the immobilized target, which can be detected by optical sensing.…”
Section: Optical Sensingmentioning
confidence: 99%